Method of lines and pseudospectral solutions of the forced korteweg-de vries equation with variable coefficients arises in elastic tube - Tay, Kim Gaik; Tiong, Wei King; Choy, Yaan Yee; Ong, Chee Tiong (Academic Publications, Ltd, 2017)
In this paper, we solved the forced Korteweg-de vries (FKdV) with variable coef- ficient arises in nonlinear wave propagation in an elastic tube with a symmetrical stenosis filled with an inviscid fluid by two numerical methods, namely method of lines and pseudospectral method. We then compared both numerical solutions with its progressive wave solution. Both methods solve FKdV equation with maximum absolute errors of 10−4.